« À l’identique ». Quelques remarques sur la notion d'authenticité en art chinois - Françoise Lauwaert (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
For many years, restoration meant reconstruction in China. Even today, the monuments destroyed by the Cultural Revolution or ultra-rapid modernization are being “remade” in order to put some soul into towns increasingly given over to commerce. The past has been swept away from towns and put on show in ever-more numerous and impressive museums. In this article I will discuss three classes of objects (monuments, bronzes and calligraphies) that occupy unequal positions in the Chinese artistic hierarchy. The question of authenticity is addressed in different terms for each of these objects. It will shed a new light on the context of the debates on the restoration and forging of works of art in the People’s Republic of China.